RESILIENSI SPIRITUAL DALAM PERSPEKTIF AL-QUR'AN: STUDI QUR'AN TEMATIK DENGAN PENDEKATAN GROUNDED THEORY - Muthoharoh; Muhammad Alif (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study aims to examine the concept of spiritual resilience from the perspective of the Qur'an and construct its conceptual model through a thematic Qur'anic approach (tafsir maudhu’i) combined with grounded theory. The primary research questions are: how does the Qur'an portray spiritual resilience? What values form its foundation? And how are these values interrelated in constructing a Qur'anic framework of spiritual resilience? This research employs a qualitative-exploratory method with data derived from selected Qur'anic verses concerning inner strength, life trials, and spiritual empowerment. The analysis was conducted through open coding, axial coding, and selective coding to develop a substantive theory grounded in scriptural texts. Findings reveal that Qur'anic spiritual resilience is built upon values such as ṣabr (patience), tawakkul (trust in God), husnuzhan (positive assumption), gratitude (syukr), and acceptance (ridha), which together form a cyclical pattern of spiritual growth. Qur’anic resilience is not passive, but active and transformative, positioning suffering as a path to spiritual maturity. The resulting model can serve as a foundation for developing Islamic counseling, character education, and Qur'an-based spiritual therapy